2020
DOI: 10.1101/2020.08.06.20169581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of the COVID-19 Pandemic on Rabies Reemergence in Latin America: the case of Arequipa, Peru

Abstract: Over the past decades, there has been tremendous progress towards eliminating canine rabies in Latin America. Major components of rabies prevention programs in Latin America leading to these successes have been constant and intense surveillance for rabid dogs and uninterrupted yearly mass dog vaccination campaigns. However, vital measures to control COVID-19 in Latin America have had the negative trade-off of jeopardizing these rabies elimination and prevention activities. In this paper, we aimed to assess the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Haiti’s 2020 dog vaccination campaign was cancelled and funds were diverted to support the COVID-19 response; funds for 2021 have not yet been identified. Similar COVID-19 related postponements to dog vaccination campaigns have also been reported in other countries 12 .…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Haiti’s 2020 dog vaccination campaign was cancelled and funds were diverted to support the COVID-19 response; funds for 2021 have not yet been identified. Similar COVID-19 related postponements to dog vaccination campaigns have also been reported in other countries 12 .…”
Section: Introductionsupporting
confidence: 80%
“…Dog rabies vaccination campaigns may be disrupted for a variety of reasons including lack of funding, political instability, or natural disasters; most recently, the COVID-19 pandemic has interrupted dog vaccination in Haiti as well as other countries 12 . We adapted a mathematical model of dog rabies transmission to assess the urgency of resuming dog vaccination campaigns in Haiti by comparing the human health and cost implications if vaccination is resumed in 2021 compared to 2022.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on response to one disease can be detrimental to the control of others, and the COVID-19 pandemic has highlighted that horizontal integration across diseases and human and animal health sectors is important and should not be overlooked. For example, a recent modelling study suggests that reduced dog vaccination and rabies surveillance due to COVID-19 control measures in Arequipa, Peru will result in increased human risk due to rabies [ 96 ]. In a broader context, it has also been suggested that frameworks for investigation and management of malaria could be extended horizontally, and used as surveillance for non-specific EID surveillance by investigating all reports of fever in people [ 97 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple researchers are raising concerns about the potential downstream impacts of the COVID-19 pandemic on the control of other diseases including HIV, tuberculosis, malaria, and neglected tropical diseases besides rabies 22,23 . A previous modeling study predicted that declines in surveillance and paused dog vaccination due to the impacts of COVID-19 could increase dog rabies cases in Peru 12 . In Haiti, the cancellation of the 2020 dog vaccination campaign was attributable to COVID-19 lockdowns and redirection of funds.…”
Section: Discussionmentioning
confidence: 99%